L’harmonie vocalique en kúsá’ál : mythe ou réalité ? Analyse du parler de zoaaga. - Nitiema, Drissa (Language Policy in Africa, 2026)
The current study, vocalic harmony in kúsá’ál (spoken by Zoaaga): alethic conception, is a contribution to explain this phenomenon phonological prove in the major part of black-africans languages and particularly in those of gur type, most precisely from kúsá’ál spoken in Burkina Faso. The analysis aims to prove the effectiveness of phonological reality in the language by describing its diverse manifestations. In order to get the evidential results, the pre-established questionnaire allowed to harvest the corpus with the informants’ speakers, natives of the study zone. This is the principle of the largest phonetic transcription which has served the development of the harvest data. We have here the standard of structural-functionalist, analysis of BONVINI (1974) for the theorization.